Research on Non-isothermal Numerical Simulation Algorithm for Tire Rubber Mixing Based on Multiphase Flow Decoupling Principle - Wang, Guolin; Wang, Jingshixiong; Zhou, Haichao; Liang, Chen (International journal of automotive technology, 2025)
Rubber mixing plays a very important role in the tire manufacturing process, and the rubber mixing effect affects the quality of the finished tire. Numerical simulation methods are often used to investigate the optimal rubber mixing parameters. To solve the problem of rubber mixing numerical simulation calculations in non-isothermal partial filling conditions when the calculation is difficult, this paper is based on the principle of decoupling to design an algorithm to calculate the rubber temperature in the rubber mixing process. The rubber viscosity and shear rate are processed using the Bird–Carreau model, and the rubber temperature and viscosity are decoupled using the Arrhenius-Law model. Define the heat generation rate of rubber based on the rubber viscosity and shear rate obtained from transient numerical simulation, and obtain the temperature value of each rubber unit. Numerical simulation calculations of rubber compounding under non-isothermal partial filling conditions are realized. To verify the feasibility of the algorithm, the designed algorithm is applied to study the effect of rubber mixing machine speed on the rubber mixing effect. Finally, comparing the numerical simulation results with the experimental results, the effectiveness of this algorithm is proven.